2020
DOI: 10.1002/ajoc.202000560
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)‐catalyzed, Picolinamide‐aided sp2 γ−C−H Functionalization of Phenylglycinol: Access to γ−C−H Arylated, Alkylated and Halogenated Phenylglycinol Scaffolds

Abstract: We report the Pd(II)-catalyzed picolinamide-aided ortho-CÀ H arylation-, alkylation-, and halogenation (sp 2 γÀ CÀ H functionalization) of phenylglycinol substrates. Phenylglycinols are remarkable building blocks and have found different applications in synthetic organic and medicinal chemistry. This work is a contribution towards the expansion of the library of phenylglycinol scaffolds and also substrate scope development by using the Pd(II)catalyzed bidentate directing group picolinamide-aided CÀ H activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…All the yields reported are isolated yields and the yields are not optimized and sometimes there is marginal variation in yields and enantiomeric ratio for the corresponding racemic/enantiopure pairs, this is perhaps based on the collection of pure fractions from the column chromatography based on the TLC and also may be due to inadvertent handling/processing errors of samples. Starting materials used in this work to carry out the Pd(II)‐catalyzed γ ‐C(sp 2 )−H alkoxylation with alcohols are known in the literature (see the supporting information) [12h,i] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the yields reported are isolated yields and the yields are not optimized and sometimes there is marginal variation in yields and enantiomeric ratio for the corresponding racemic/enantiopure pairs, this is perhaps based on the collection of pure fractions from the column chromatography based on the TLC and also may be due to inadvertent handling/processing errors of samples. Starting materials used in this work to carry out the Pd(II)‐catalyzed γ ‐C(sp 2 )−H alkoxylation with alcohols are known in the literature (see the supporting information) [12h,i] …”
Section: Methodsmentioning
confidence: 99%
“…A literature survey on the Pd(II)‐catalyzed DG‐aided ortho γ ‐C(sp 2 )−H functionalization of enantiopure α ‐alkylbenzylamine derivatives revealed that limited examples of alkylation, alkynylation, carbonylative cyclization, etc have been documented [12] . Along this line, we recently reported the Pd(II)‐catalyzed picolinamide‐aided ortho ‐C−H arylation/alkylation/halogenation of racemic and enantiopure α ‐methylbenzylamine and phenylglycinol scaffolds involving C−C, C−Br and C−I bond‐forming reactions [12h,i] …”
Section: Introductionmentioning
confidence: 99%